2014
DOI: 10.1128/mcb.00348-14
|View full text |Cite
|
Sign up to set email alerts
|

The Leukocyte Activation Receptor CD69 Controls T Cell Differentiation through Its Interaction with Galectin-1

Abstract: f CD69 is involved in immune cell homeostasis, regulating the T cell-mediated immune response through the control of Th17 cell differentiation. However, natural ligands for CD69 have not yet been described. Using recombinant fusion proteins containing the extracellular domain of CD69, we have detected the presence of a ligand(s) for CD69 on human dendritic cells (DCs). Pulldown followed by mass spectrometry analyses of CD69-binding moieties on DCs identified galectin-1 as a CD69 counterreceptor. Surface plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 41 publications
(51 reference statements)
4
65
0
2
Order By: Relevance
“…More recently, the DC‐derived galectin‐1 ligand was shown to negatively regulate T helper (T h )17 effector cell differentiation via CD69 (24), whereas the positive expression of CD69 in Foxp3 + T reg cells was shown to maintain immune tolerance (8). However, the role of CD69 in the switch of CD4 + naive T cells into CD25 + Foxp3 + T reg cells has yet to be elucidated.…”
mentioning
confidence: 99%
“…More recently, the DC‐derived galectin‐1 ligand was shown to negatively regulate T helper (T h )17 effector cell differentiation via CD69 (24), whereas the positive expression of CD69 in Foxp3 + T reg cells was shown to maintain immune tolerance (8). However, the role of CD69 in the switch of CD4 + naive T cells into CD25 + Foxp3 + T reg cells has yet to be elucidated.…”
mentioning
confidence: 99%
“…6D). Given the fact that galectin‐1, a β‐galactoside‐binding immune‐suppressive protein, has recently been discovered as a ligand for CD69 on DCs [34], the presence of Gal‐1 on MultiStem was also studied. Fluorescence microscopy revealed Gal‐1 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the MultiStem‐mediated elevated levels of CD69 in T cells and the presence of its ligand Gal‐1 [34] in MultiStem, Gal‐1/CD69 binding could be an important mechanism of immune modulation by adult stem cells, independent of cytotoxicity suppression. de la Fuente et al already proved inhibition of T h 17 differentiation and function in mice and humans upon CD69 recruitment [34]. In our study, we demonstrated that Gal‐1 signaling did not mediate the inhibitory effect of MultiStem on T‐cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Gal-1-expressing DCs greatly contributed to the resolution of antigen-specific and autoimmune diseases [93]. Although the precise molecular mechanisms involved in this effect still remain to be explored, recent studies identified CD69 as a counter-receptor for DC-derived Gal-1 on T cells, suggesting that a Gal-1-CD69 axis may contribute to DC-mediated suppression of pro-inflammatory T cell responses [98]. Moreover, DC expression of Gal-1 mediates, at least in part, the tolerogenic effects triggered by IL-10 and apoptotic cells [99,100].…”
Section: Tolerogenic Dendritic Cellsmentioning
confidence: 99%